2000
DOI: 10.1097/00005768-200002000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abstinence from cigarette smoking on the cardiorespiratory capacity

Abstract: In conclusion, exercise performance was improved by the 7 d of abstinence from smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…Hashizume et al (2000) reported 7 days of abstinence from smoking could improve exercise performance, and Suminski et al (2009) recommended that smoking should be considered when using non-exercise models to estimate maximal oxygen uptake. In the present study, maximal oxygen uptake was higher in non-smokers, and smoking was a significant variable in multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashizume et al (2000) reported 7 days of abstinence from smoking could improve exercise performance, and Suminski et al (2009) recommended that smoking should be considered when using non-exercise models to estimate maximal oxygen uptake. In the present study, maximal oxygen uptake was higher in non-smokers, and smoking was a significant variable in multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The factors associated with maximal oxygen uptake included genetics, age, gender, physical activity, body fat, smoking and medical conditions such as metabolic syndrome and diabetes (O'Tool 1989;Watanabe et al 1994;Chilibeck et al 1996;Kawabata et al 1997;Lim et al 1997;Hashizume et al 2000;Park et al 2001;Zhang et al 2004;An et al 2005;Kang et al 2005). Considering ethnical difference on maximal oxygen uptake, it is necessary to develop a non-exercise regression model for Korean adults (John et al 2011).…”
mentioning
confidence: 99%
“…Moreover, exercise capacity increases very shortly after smoking cessation, arguing for a direct role of smoking in the diminution of exercise capacity 3. Impaired exercise capacity is related to poor quality of life, reduced physical function, inability to complete activities of daily living and increased dependence 4,5.…”
mentioning
confidence: 99%
“…Although several studies of smoking cessation have not reported short-term changes in lung function [24,25], a decreased vital capacity has been observed after 1 week [26]. Increased lung function values, vital capacity and FEV ".!…”
Section: Discussionmentioning
confidence: 99%